Teachers’ Lived Experiences on Collaboration in Online Teacher Education: A Phenomenological Study (Journal of Bhuwanishankar, 2024)
This research aimed to explore the English language teachers’ lived experiences of collaboration in teacher education via online mode. This study embraced a phenomenological qualitative research design and involved four English teachers purposively to gather their lived experiences on the phenomena. Informal discussions and semi-structured interviews were used to gather data. Using the Hermeneutic phenomenological method, the data were analyzed. This study used Vygotsky's Social Constructivism as its theoretical foundation (1978). The findings demonstrate that English language teachers have positive perspectives and collaboration experiences in online teacher education. The collaboration develops their confidence, critical analysis, technological skills, and rapport building. The participants expressed that collaboration in teacher education reduces the workload and stress if all the members are equally responsible for the completion of their tasks. However, the division of work constrains the members into their parts only resulting the less exploration and knowledge construction in others’ portions.